Analysis of the Casemix Team Performance on the Quality of Health Services and Outpatient Patient Satisfaction at Grandmed Hospital in 2025 - Anggi Kurnia Ningsih; Rahmadani Sitepu; Tati Murni Karo Karo (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
The The implementation of the Casemix system through INA-CBG’s as part of the National Health Insurance (JKN) program requires hospitals to improve efficiency while maintaining service quality. The performance of the Casemix team plays a crucial role in ensuring coding accuracy, claim timeliness, and cost control. This study aimed to analyze the factors influencing the performance of the Casemix team and its relationship with service quality in the Outpatient Unit of RS Grandmed Lubuk Pakam in 2025.This research used a mixed methods approach with a sequential explanatory design. Quantitative data were collected from 93 JKN outpatient respondents selected using the Slovin formula and accidental sampling technique. Data were analyzed using univariate, bivariate (Chi-Square test), and multivariate (multiple logistic regression) analyses. Qualitative data were obtained through in-depth interviews with five key informants selected purposively and analyzed using thematic analysis.The results showed that most respondents rated human resources (62.4%), SIMRS-based Casemix system (65.6%), facilities and infrastructure (59.1%), financing (67.7%), service quality (64.5%), and Casemix team performance (63.4%) in the good category. Bivariate analysis indicated that all independent variables had a significant effect on Casemix team performance (p < 0.05). Multivariate analysis revealed that service quality was the most dominant factor influencing Casemix team performance (OR = 6.46; p = 0.000), followed by human resources (OR = 4.10; p = 0.002) and financing (OR = 3.44; p = 0.006). In conclusion, the success of Casemix implementation in the outpatient unit is influenced by a combination of human resources, information systems, financing mechanisms, and service quality. Strengthening human resource competence and improving service quality are key strategies to optimize Casemix team performance and enhance hospital service efficiency